2010
DOI: 10.1614/wt-09-070.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Addition and Weed Interference on Soil Nitrogen and Corn Nitrogen Nutrition

Abstract: Weeds cause crop loss indirectly by reducing the quantity of resources available for growth. Quantifying the effects of weed interference on nitrogen (N) supply, crop growth, and N nutrition may assist in making both N and weed management decisions. Experiments were conducted to quantify the effect of N addition and weed interference on soil nitrate-N (NO3-N) over time and the dependence of corn growth on NO3-N availability, determine the corn N nutrition index (NNI) at anthesis, and evaluate if relative chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
(38 reference statements)
3
18
0
Order By: Relevance
“…The full N rate resulted in a 56.5 and 45.6 mg m -2 increase in corn leaf chlorophyll content over the reduced N rate at the V11 and V14 growth stages, respectively. Our results are consistent with previous studies that have demonstrated the positive correlation between corn leaf chlorophyll content and N application rates (Lindquist et al, 2010;Ziadi et al, 2008;Scharf et al, 2006). Additionally, lower R:FR at the V5 growth stage correlated with lower corn leaf chlorophyll content at the V8 and V14 growth stages in the full N rate treatments (data not shown).…”
Section: Notesupporting
confidence: 93%
“…The full N rate resulted in a 56.5 and 45.6 mg m -2 increase in corn leaf chlorophyll content over the reduced N rate at the V11 and V14 growth stages, respectively. Our results are consistent with previous studies that have demonstrated the positive correlation between corn leaf chlorophyll content and N application rates (Lindquist et al, 2010;Ziadi et al, 2008;Scharf et al, 2006). Additionally, lower R:FR at the V5 growth stage correlated with lower corn leaf chlorophyll content at the V8 and V14 growth stages in the full N rate treatments (data not shown).…”
Section: Notesupporting
confidence: 93%
“…N content in biomass was below Ncrit and NNI was below 1.0 from 105 DAP (tasseling) to harvest under rainfed and 50% FIT and from 114 DAP (silkinggrain fill stage) to harvest under 60% FIT (Figure 3). NNI was higher earlier in the season and decreased with time due to interspecific and intra-specific competition for soil N (Jensen, 1996; Article Corre- Hellou et al, 2006;Bedoussac and Justes, 2009;Lindquist et al, 2010). This showed that crops were under non-limiting nitrogen supply conditions during their vegetative stage up to flowering stage under all irrigation regimes.…”
Section: Evaluation Of Critical Nitrogen Model and Nitrogen Nutritionmentioning
confidence: 93%
“…Early in the growing season, weeds can accumulate N rapidly, which can contribute to early-season interference and subsequent yield loss in corn (Zea mays L.) (Teyker et al, 1991;Davis & Liebman, 2001;Evans et al, 2003aEvans et al, , 2013bCathcart & Swanton, 2004;Harbur & Owen, 2004;Lindquist et al, 2010), wheat (Triticum aestivum L.) (Blackshaw et al, 2002;Blackshaw et al, 2004), rice (Oryza sativa L.) (Ampong-Nyarko & De Datta, 1993a, 1993b, and canola (Brassica napus L.) (Blackshaw et al, 2011). Weeds can reduce soil NO 3 -N up to 50% in corn (Lindquist et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Weeds can reduce soil NO 3 -N up to 50% in corn (Lindquist et al, 2010). Several integrated weed management studies (Walker & Buchanan, 1982;Di Tomaso, 1995) have investigated nitrogen because direct uptake by weed species may affect control (Kim et al, 2006) and grain yields depending on fertilizer rate (Evans et al, 2003a(Evans et al, , 2003bCathcart & Swanton, 2004;Lindquist et al, 2010), placement (Blackshaw et al, 2002;Blackshaw et al, 2004), timing (Blackshaw et al, 2004;Harbur & Owen, 2004), and source (Teyker et al, 1991;Davis & Liebman, 2001;Blackshaw et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation